Euro Under Crossfire. Will the European Monetary Union Survive? - Roxana Paraschiv (CES Working Papers, 2011)
The creation of the European Monetary Union was both a political and an economic decision considered to be a success for almost a decade. Starting from 2008-2009, the EMU has been facing the most difficult moments of its existence. This paper aims at analyzing the impact of the current financial crises on the EMU member countries, the measures taken up to the present as a response to the crises and the future perspective for the European single currency. Both the breaking up of the EMU and its maintaining prove to be costly decisions. The recent evolutions have shown the political will to keep the EMU together, but we must ask ourselves at what price and risk.
Keywords: F15; F36; E58; 330; European Monetary Union; euro; financial crisis Romania